A seven item scale for the assessment of disabilities after child and adolescent injuries. Issue 2 (June 1997) - Gofin, R.; Adler, B.
Abstract : OBJECTIVES: To develop a scale to assess physical disabilities after child or adolescent injuries. SETTING: The three main hospitals of Jerusalem. METHODS: Telephone interviews pertaining to the injury's effect on the functioning of children 4-17 years old (n = 281) were carried out six months after an injury. Disabilities were recalled by the parents for the period immediately after the injury (short term) and at the time of interview (long term). Of 25 questions derived from the International Classification of Impairments, Disabilities and Handicaps, seven were selected: limitations in walking, running, getting up/lying down, moving in bed, going to the toilet, bathing/keeping personal hygiene, and dressing. Construct validity was tested using the usual, sport, school, and leisure time activities as the gold standard. RESULTS: The prevalence of short term disabilities ranged from 23.8% to 37.7% and of long term disabilities from 0.4% to 11.8%. Cronbach's alpha was 0.91 for the short term scale and over 0.90 for the different categories of the sociodemographic variables. It decreased to 0.66 for the long term scale. Sensitivity of the short term scale ranged from 77% to 89%, but was lower for the long term scale. Specificity varied from 72% to 84% and increased to 88% to 90%, six months after the injury. CONCLUSIONS: This scale could be used to study disability after injury among children and adolescents in different cultures. It is a simple method that does not require expert personnel and has relatively high validity and internal reliability.